Communication Planning: A Tool for Behavior Change - Putri, Ardhya; Oktaviani, Rani C. (LSPR Institute of Communication & Business, 2022)
Communication plan is an essential element to create a communication strategy that will support the success of the project. In the other hand, a clear objective has to be defined in order to set the message that is going to deliver. If the objective is to change behavior is more challenging. In this paper, I will use ADKAR (Awareness, Desire, Knowledge, Action and Reinforcement) by Prosci method, to create a comprehensive communication plan for reducing numbers of child abduction in Jakarta.